Large-Cell Transformed Mycosis Fungoides Coexisting with Mycosis Fungoides Bullosa: A Case Report and Review of the Literature - Saneerat Porntharukcharoen; Suthinee Rutnin; Natta Rajatanavin (Karger Publishers, 2017)
Mycosis fungoides is the most common form of cutaneous T-cell lymphoma. Both large-cell transformed mycosis fungoides and mycosis fungoides bullosa are rare presentations and predict unfavorable prognosis. We report the case of a 61-year-old woman who presented with generalized erythematous scaly annular plaques, and histopathology confirmed the diagnosis of mycosis fungoides. She was treated with various conventional therapies but only achieved partial response and always relapsed after discontinuation of treatment. Her last treatment was combined chemotherapy (CHOP regimen) followed by romidepsin. However, 1 month after the last cycle of romidepsin, she developed multiple ulcerative masses and nodules. Skin biopsy was compatible with CD30+ large cell transformation, and she was treated with a new combination of chemotherapy (ifosfamide, carboplatin, etoposide). One day after receiving chemotherapy, multiple tense bullae on normal-appearing skin and mycosis fungoid plaques erupted. A histological study demonstrated subepidermal blistering with epidermotropism of atypical lymphocytes. Direct immunofluorescence study was negative. The results confirmed the diagnosis of mycosis fungoides bullosa. We present the first reported case of large-cell transformed mycosis fungoides coexisting with mycosis fungoides bullosa.